2021
DOI: 10.3390/children8080682
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of SARS-CoV-2 Rapid Antigen Test in a Large, German Cohort

Abstract: We assessed the performance of a rapid antigen test (RAT) in everyday clinical practice. Between 1 November 2020 until 1 April 2021 all in-patients at the Helios University Hospital Wuppertal, Germany, as well as the accompanying relatives at the Children’s Hospital received a SARS-CoV-2 RAT and a SARS-CoV-2 RT-PCR prior to admission. Out of 3686 patients, 22 (0.6%) subjects were tested positive by RT-PCR and RAT, and 3591 (97.4%) were negative by both methods, showing discordant results: RT-PCR+/RAT− in 58 (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 43 publications
2
9
0
Order By: Relevance
“…The relatively low sensitivity observed in our study for both Ag-RDTs could be attributed to several factors, including deficient specimen collection [ 10 ], test performance, and patients’ clinical characteristics, including their viral loads [ 16 ]. Our study also observed a lower sensitivity (<35%) in asymptomatic cases, similar to those observed in other reports [ 22 , 24 ], that are probably associated with lower viral loads in those patients [ 4 , 20 ]. Evaluations in Europe and America observed a higher sensitivity of Ag-RDTs when compared to studies in Asia and Africa.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relatively low sensitivity observed in our study for both Ag-RDTs could be attributed to several factors, including deficient specimen collection [ 10 ], test performance, and patients’ clinical characteristics, including their viral loads [ 16 ]. Our study also observed a lower sensitivity (<35%) in asymptomatic cases, similar to those observed in other reports [ 22 , 24 ], that are probably associated with lower viral loads in those patients [ 4 , 20 ]. Evaluations in Europe and America observed a higher sensitivity of Ag-RDTs when compared to studies in Asia and Africa.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the results obtained from Cohen’s kappa coefficient analysis showed better agreement in symptomatic patients, with symptoms 1 to 5 days before the test, thus reinforcing better applicability of both RDTs in this group of patients [ 21 ]. Another study, performed by Mboma et al (2021), found an overall sensitivity of 30.4% (95%CI: 18.8–90.9%) in adults attending a hospital being higher at 52.9% in symptomatic cases [ 22 ]. Furthermore, Jegerlehner et al (2021), in a different study, found an overall sensitivity of 65.3% (95% CI: 56.8–73.1) and 44.4% (95% CI 24.4–65.1) in asymptomatic cases [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The specificity was excellent. With the right cut-off the RAT can be useful to distinguish SARS-CoV-2-infected subjects who can transmit the infection from noninfectious people, enabling appropriate triage while waiting for the RT-PCR result [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…While some asymptomatic screening programs have been described in the literature ( 12 15 ), they have been limited in size and scope or have been focused on contextually different settings outside of workplaces ( 16 ) , including clinical settings ( 17 ). Furthermore, other large-scale screening programs that have a serial design (i.e., regular, frequent screening rather than ad hoc or one-time testing) have not had their implementation process systematically described, data collected, nor even suggestive evidence of their efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Without asymptomatic testing, there are no other ways to detect these infectious individuals until they become symptomatic, after which spread could have already occurred, and the ability to test-trace-isolate is substantially hindered (6,7). The larger consequence of this information gap is that these infectious cases contribute to spread, uncontrolled transmission, and workplace shutdowns (5,(10)(11)(12)(13). Rapid antigen screening for COVID-19 provides useful information on who is likely to be infectious (11), and information can be gained in real time to proactively manage infectious individuals, particularly when serial screening (e.g., at least two times weekly) is one of several layers of protection alongside others such as vaccination, masking, physical distancing, and ventilation (1).…”
Section: Introductionmentioning
confidence: 99%